2007
DOI: 10.1016/j.cellbi.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in composition and activities of 26S proteasomes under the action of doxorubicin—apoptosis inductor of erythroleukemic K562 cells

Abstract: Changes in the subunit composition, phosphorylation of the subunits, and regulation of the activities of 26S proteasomes in proliferating cells undergoing programmed cell death have not been studied so far. Moreover, there are no reports on phosphorylation of proteasome subunits both in normal and in neoplastic cells during apoptosis. The data of the present study show for the first time that apoptosis inductor doxorubicin regulates subunit composition, enzymatic activities, and phosphorylation state of 26S pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…NFAT5 has been reported to play a role in cardiomyocyte survival [49,50]. Previously, Dox induced apoptosis have been suggested to result from proteasome-mediated degradation of NFAT5 [44–51]. In the current study, we found a significant increase in NFAT3 and a decrease in NFAT5 levels in myocardial tissue from Dox treated animals.…”
Section: Discussionsupporting
confidence: 71%
“…NFAT5 has been reported to play a role in cardiomyocyte survival [49,50]. Previously, Dox induced apoptosis have been suggested to result from proteasome-mediated degradation of NFAT5 [44–51]. In the current study, we found a significant increase in NFAT3 and a decrease in NFAT5 levels in myocardial tissue from Dox treated animals.…”
Section: Discussionsupporting
confidence: 71%
“…Dox has been shown to both inhibit and activate UPS proteolytic activities in experimental settings (10,24,45). The present study reveals that a critical factor for this dichotomy is likely the dosage of Dox.…”
Section: Discussionmentioning
confidence: 71%
“…Dox and its metabolites induced posttranslational modifications to UPS substrates, and proteasome subunits may also play a role in its effects on UPS-mediated protein degradation. Tsimokha et al (45) recently reported that Dox treatment can increase the phosphorylation of proteasome subunits and enhance the chymotrypsinlike activity of the 26S proteasome in cultured neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasomes were extracted and purified from cytosol using a multistep purification procedure as described previously [56]. …”
Section: Methodsmentioning
confidence: 99%